Anaerobic Strength and Power in Master Athletes - Gacesa, Jelena (Sports Medicine International Open, 2017)
The study compared anaerobic capacity and power in master athletes of different ages, and correlated 2 different anaerobic tests. The study was conducted on 60 male athletes: group I 30–35 years (n1=35, age 32.23±1.53 y), group II 35–45 years (n2=15, age 39.17±3.60 y), group III above 46 years (n3=10, age 52.13±4.50 y). The Wingate anaerobic test and ergometry of elbow flexors, elbow extensors, and knee extensors were performed. Average peak anaerobic power (PP) in group I was 692.94±216.53 W, in group II 593.40±185.91 W, non-significantly lower by 14.4% (p>0.05). In group III, PP was 381.50±117.62 W, significantly lower by 44.9% when compared with group I (p≤0.001). Ergometry parameter of muscle strength and power showed greater decline with age (up to 32.3%) in comparison with contraction velocity (up to 14.1%). Significant correlation was registered between PP and ergometric parameter power for knee extensors (KE) (PP/KE power: r was 0.59 in group I, 0.85 in group II, and 0.90 in group III, p≤0.05). Master athletes represent an interesting population for studying the chronic effects of physical activity on functional capacity changes during ageing. Strength parameters “age” in different fashion, because the contraction velocity parameter is less influenced than strength by the muscle alterations with increasing age.
Keywords: anaerobic power; strength; WAnT; ergometry; master athletes; ageing